Learning Transformation: Effective Strategies for Transforming Ordinary Elementary School Classrooms into Interactive Math Labs - Latri, Latri; Juhari, Agusalim (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Textbook lectures and exercises typically dominate elementary school mathematics, which diminishes student enthusiasm and conceptual understanding. Students have trouble applying arithmetic to real life in non-visual, kinesthetic classrooms. Thus, this project seeks to create and implement a plan to turn primary school classrooms into engaging mathematics laboratories at SPF Unit of Tidung State Elementary School. Students' active participation and conceptual mastery of math are the goals. This study employs two cycles of Classroom Action Research (CAR). The transformation strategy includes 1) creating a Mathematics Corner with manipulatives, 2) using classroom walls as interactive visual media (posters and mind maps), and 3) implementing a Project-Based Learning (PjBL) Model in the new classroom. Monitoring student involvement, learning outcome tests, and student and instructor reaction questionnaires provided data. The study found that the transformation strategy provided an active and responsive learning environment. Student participation in mathematical exploration activities rose from 65% in cycle I to 88% in cycle II. Environmental intervention increased conceptual understanding by 15%. Mathematics was more appealing to students. This study demonstrates to primary schools, particularly those in urban areas, how to transform limited classroom space into a math laboratory without incurring significant costs. Its theoretical contribution strengthens empirical evidence that an interacting physical environment motivates and increases primary school pupils' math achievement.